(untitled) (Research, Society and Development, 2021)
Vinegar is characterized as a dilute solution based on acetic acid, established by two processes: alcoholic fermentation, when sugar is changed to ethanol; and fermentative oxidation, converting alcohol into acetic acid. Thus, throughout history, it has been used as a condiment and food preservative, in addition to being constituted by nutritional and bioregulatory properties identified as fundamental complements in food. Vinegar can manifest positive physiological effects related to blood pressure regulation, blood glucose control, aid in digestion and appetite stimulation. The aim of the study was to evaluate the quality of samples of vinegars sold in Manaus. Five samples of vinegars of different brands identified as samples A, B, C, D, E, found in commercial establishments in the city of Manaus-AM, from September to October 2021, were randomly selected. The acetic acid content in vinegars was quantified following methodology adapted from Baccan, 2001. The acetic acid content quantified in vinegars ranged from 3.08% to 4.57%. Samples C, D and E presented acidity values ​​below the established standard, the others presented acidity values ​​in accordance with what is recommended by the legislation in force.